ISLEW PROCESINDE JELINGEN DETALLARDI TEMIR ÓSIRIW JOLÍ MENEN QAYTA TIKLEW - Dawletmuratov, B.; Atashov, D. (SCIENCE and SOCIETY, 2023)
The article deals with the restoration of worn parts from electrolytic glands. Conducted the preparation of the technology of chemical solution and electrode, electrolyte for the restoration of worn parts, with a galvanic method.